Optimizing differentiation and commonality levels among models in car line-ups: An empirical application of a nature-inspired heuristic mechanism. Issue 5 (1st April 2015) - Saridakis, Charalampos; Tsafarakis, Stelios; Delias, Pavlos; Baltas, George; Matsatsinis, Nikolaos
Highlights We implement a swarm intelligence mechanism to design optimal car lines. We aim to optimize differentiation and commonality levels among models in the line. Our mechanism utilizes stated preference data derived from a conjoint experiment. A prototype system is also developed to facilitate managerial decision making. Insights are provided into how new and existing car models must be combined.